Structural racism and the health of Palestinian citizens of Israel - Osama Tanous; Yara Asi; Weeam Hammoudeh; David Mills; Bram Wispelwey (Taylor & Francis Group, 2023)
Palestinian citizens of Israel (PCI) constitute almost 20% of the Israeli population. Despite having access to one of the most efficient healthcare systems in the world, PCI have shorter life expectancy and significantly worse health outcomes compared to the Jewish Israeli population. While several studies have analysed the social and policy determinants driving these health inequities, direct discussion of structural racism as their overarching etiology has been limited. This article situates the social determinants of health of PCI and their health outcomes as stemming from settler colonialism and resultant structural racism by exploring how Palestinians came to be a racialized minority in their homeland. In utilising critical race theory and a settler colonial analysis, we provide a structural and historically responsible reading of the health of PCI and suggest that dismantling legally codified racial discrimination is the first step to achieving health equity.